Analysis of Wal-Mart’s Success in the Chinese Retail Market - Chen, Chenwei (2016)
Expanding into other countries can be a good way for companies to grow, as companies face more and more competitive business environment in the domestic market. Companies try to go abroad to find more resources and developmental opportunities. China, as an emerging Asian market attracts many retailers to invest. World retailers, like Wal-Mart of the US, Tesco of the UK and Carrefour of the France are all trying to expand in Chinese market. In fact, during these expansive processes, retailers may face a lot of unpredictable challenges. Ultimately, some retailers succeed, while some failed. This dissertation tries to analyze Wal-Mart’s success in China through comparing with the other two cases, which are Tesco’s failure in China and Wal-Mart’s failure in Japan. Through the whole dissertation, I will organize the whole research from several aspects, which may include internal factors within companies, external factors from foreign markets, and some strategies that are applied by companies in target markets. Finally, according to the data analysis, conclusions will be drawn in order to identify which factors and strategies are important for Wal-Mart’s success in Chinese retail market.